Factors Relate to Personal Hygiene of Traders at Busalangga Market Rote Barat Laut district - Henukh, Tresna Asriany; Manurung, Imelda F. E.; Limbu, Ribka (Faculty of Public Health, Nusa Cendana University, 2025)
This study aims to identify factors related to personal hygiene of traders at Busalangga Traditional Market, Rote Barat Laut District. Given the high number of diseases related to personal hygiene in Rote Ndao. Data from the Rote Ndao Health Office in 2022 with a total of 3,522 cases of ISPA,1,192 cases of allergic skin diseases, 398 cases of diarrhea and several diseases such as influenza, urticaria, laryngitis, bronchopneumonia, this study uses a quantitative approach with a cross-sectional design. Data were collected through questionnaires distributed to 64 respondents who were randomly selected from a population of 186 traders. The results of the analysis showed that there was a significant relationship between age and personal hygiene of traders with a p value of 0.049, education with personal hygiene of traders with a p value of 0.028, knowledge with personal hygiene of traders with a p value of 0.026. However, there was no significant relationship between attitude and personal hygiene of traders with a p value of 0.054 and the availability of personal hygiene facilities with personal hygiene of traders with a p value of 0.276. This study is expected to provide useful information for health agencies and the community to increase awareness of the importance of personal hygiene, as well as being a reference in community health development programs in traditional markets.